Syntactic Coordination of Compound Sentences Found in Sasaknese Children’s Books - Hijriati, Sartika; Herayana, Desi (Universitas Muhammadiyah Mataram, 2026)
This qualitative generative syntactic study investigates the types of coordination in compound sentences found in Sasaknese children’s books Nyale leq Tian Manusie and Dende Mirah Buaq Ate Kembang Mate. The analysis applies Quirk and Greenbaum’s classification of coordination and employs Chomsky’s X-bar theory to examine the syntactic structures of coordinated clauses. The findings show that Sasaknese employs both syndetic coordination, marked by conjunctions such as laguq ‘but’, dait ‘and’, and terus ‘so’, and asyndetic coordination, which is realized through clause juxtaposition marked by commas. X-bar analysis demonstrates that each coordinated clause independently projects an Conjunction Phrase (ConjP) as the head of IPs, confirming syntactic equality within coordination.